2020
DOI: 10.1021/acsomega.9b04433
|View full text |Cite
|
Sign up to set email alerts
|

New Type Biomembrane: Transport and Biodegradation of Reactive Textile Dye

Abstract: In traditional separation processes, there are environmental risks still because of the presence of toxic agents. Thus, a novel biomembrane microreactor named eco-green biomembrane (EgBM) was developed to perform the transport, biodegradation, and cleaning of a textile dye aqueous solution (3 mg/L) from the donor (i.e., textile dye) to the acceptor (i.e., laccase enzymes) phases. In the present work, Morchella esculenta pellets were used as carriers and degraders instead of using the traditional chemical carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Reactive dyes are soluble in water, and 5-10% of these dyes enter the dye bath and are present in the colored effluent, which creates serious problems for the environment (Hynes et al 2020). Removal of reactive dyes and their degradability in biological systems using conventional wastewater treatment techniques is low (Dayı et al 2020). For this reason, focusing on specific methods of removing dye from industrial effluents helps to select a treatment system appropriate to the type of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive dyes are soluble in water, and 5-10% of these dyes enter the dye bath and are present in the colored effluent, which creates serious problems for the environment (Hynes et al 2020). Removal of reactive dyes and their degradability in biological systems using conventional wastewater treatment techniques is low (Dayı et al 2020). For this reason, focusing on specific methods of removing dye from industrial effluents helps to select a treatment system appropriate to the type of pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The stretching vibration of C=N groups were observed at 1030, 1239, 1589 cm −1 in FTIR and 1031, 1257, 1590 cm −1 in FTRaman and scaled calculated bands at 1045, 1216, 1264, 1319, 1437, 1504, 1554, 1601 cm −1 for CCPEHP molecule. The C-H stretching vibrations in compounds containing aromatic groups are generally in the range 3000-3100 cm −1 [ 51 , 52 ]. The absorption peaks at 3069 and 3025, 3055 cm −1 were assigned to the FTRaman and FTIR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Study on the mycoremediation of dyes is not limited to the above demonstrated works. There are a significant numbers of research works in which fungal sources have been successfully utilized in the dyes degradation, decolorization and detoxification studies (Al‐Tohamy et al, 2020; Ben et al, 2020; Bu et al, 2020; Dayı et al, 2020; Eichlerová & Baldrian, 2020; Karim et al, 2020; Purnomo & Mitha Ocdyani Mawaddah, 2020; Ramadhan et al, 2021; Sharma et al, 2017; Sowjanya et al, 2020). Table 1 shows the involvements of various fungi in the remediation of different dyes.…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%